PENGEMBANGAN KOLEKSI DIGITAL DI PERPUSTAKAAN FAKULTAS KEDOKTERAN UNIVERSITAS PENDIDIKAN GANESHA: Koleksi Digital - Gede Wisnu aryawan; Prof.Dr. Drs. I Wayan Mudana; I Putu Putra Yana Wardana (ACARYA PUSTAKA, 2026)
This study aims to examine the development of digital collections at the Faculty of Medicine Library, Ganesha University of Education, including the development process, user utilization, obstacles encountered, and solutions implemented to overcome these obstacles. The study used a qualitative method with a descriptive approach. Data collection was conducted through observation, interviews, and document studies. Research informants were determined using purposive sampling and snowball sampling techniques. The data obtained were analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results of the study indicate that digital collection development is carried out as a solution to the limitations of printed collections. Digital collections are developed through the utilization of digital documents obtained from donations, then processed into collections that can be accessed publicly. The existence of digital collections provides benefits for users because it facilitates access to information, speeds up the collection search process, and supports learning and research activities. Obstacles faced include budget limitations, inadequate technological devices, and limited collections relevant to the field of excellence. To overcome these obstacles, librarians coordinate with faculty leaders and build on the development of digital collections. The results of the study indicate that collaboration and institutional support are important factors in the success of digital collection development in higher education libraries.